NGHIÊN CỨU KHẢ NĂNG CHỐNG CHỊU VÀ HẤP THU CHÌ Pb, Zn CỦA DƯƠNG XỈ PTERIS VITTATA L. - Tựa, Trần Văn; Kiên, Nguyễn Trung; Anh, Đỗ Tuấn; Kim, Đặng Đình (Vietnam Journal of Science and Technology, 2012)
Phytoremendiation is a new treatment technique in pollution which has been studying and developing in recent years. In comparison to the other techniques, this is proved to be more effective, economical and be able to prevent negative consequences. The results from the experiment named “the study about the resistibility and absorptivity  of the Pteris vittata fern to Pb and Zn” have shown that Pteris vittata can be able to resist Pb contained in the earth at a concentration of 3000 mg/kg, despite the fact that  its best level of Pb resistance and absorptivity is less than 1000 mg/kg of earth. In the case of Zn, this fern species can withstand to a concentration of 1500 mg/kg of earth. Whereas, Pteris Vittata can absort and store up the most when the Zn concentration in earth is 300 mg/kg. The content of Pb and Zn in fronds and roots of Pteris Vittata increases when the concentration of these two elements in earth rises up. Pteris vittata’s ability to store Pb and Zn is reduced by time, however, the effectiveness to eliminate these two elements increases as a consequence of increasing its biomass.